Disability Empowerment in the Perspective of Collaborative Governance in Kampar District - Steven Anthony; Iqbal Miftakhul Mujtahid; Auradian Marta; Baskoro Wicaksono; Musa Thahir (Ridwan Institute, 2023)
The capacity of local governments to empower persons with disabilities is still limited and not optimal, therefore it requires a collaborative approach involving all stakeholders in the region. Empowerment of individuals and communities with disabilities in Kampar District is not carried out continuously, fragmented, and has not been implemented holistically. In fact, the design of institutions in community empowerment is also unclear so that the disability community does not get their rights. The purpose of this study is to describe the policies carried out by the local government of Kampar Regency in fulfilling the rights of people with disabilities and the impact of these policies from the perspective of collaborative governance. This study uses a qualitative research approach using data collection techniques in the form of interviews and document review. The analysis used in this study adapts to the case study approach, which is to build explanations by collecting information from (many) different sources to then be discussed and analyzed with relevant theories and clear statements. Based on the results of the study, it was found that (1) empowerment from the perspective of participation in disability empowerment is still very minimal, especially the involvement of the private sector in empowering, disability empowerment in Kampar Regency in the perspective of collaborative governance has not shown optimal results, (2) disability empowerment in Kampar Regency in the perspective of collaborative governance has not shown optimal results, (3) the facilitative leadership aspect has also not shown its role in gathering all parties and potential resources available in empowering people with disabilities. Therefore, this study recommends the importance for local governments to expand networks, communication, coordination and intensive and sustainable cooperation with various stakeholders, both public and private, to strengthen regional disability programs.